2021
DOI: 10.1016/j.neuroimage.2021.118708
|View full text |Cite
|
Sign up to set email alerts
|

Recording brain responses to TMS of primary motor cortex by EEG – utility of an optimized sham procedure

Abstract: Highlights Optimized sham TMS-EEG is introduced and tested. Sham combined auditory and supramaximal electrical somatosensory stimulation. Subjects reported equal sensory perception during sham and real TMS. Subtraction revealed evoked EEG potentials and beta-band power specific to real TMS. The optimized sham procedure is relevant in research and therapeutic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 62 publications
(133 reference statements)
7
71
2
1
Order By: Relevance
“…In keeping with a growing literature [27,[45][46][47][48], correlation analysis showed that TEPs generated by cortical stimulation and peripherally-evoked potentials (PEPs) generated by shoulder stimulation tended to show similarities from ~70 ms post-TMS. This correlation has been suggested to reflect increased sensory contamination of the later TEP components, principally due to the auditory and somatosensory stimulation generated by TMS [45,47].…”
Section: Considerations For Sensory Contamination Within the Tepsupporting
confidence: 65%
See 1 more Smart Citation
“…In keeping with a growing literature [27,[45][46][47][48], correlation analysis showed that TEPs generated by cortical stimulation and peripherally-evoked potentials (PEPs) generated by shoulder stimulation tended to show similarities from ~70 ms post-TMS. This correlation has been suggested to reflect increased sensory contamination of the later TEP components, principally due to the auditory and somatosensory stimulation generated by TMS [45,47].…”
Section: Considerations For Sensory Contamination Within the Tepsupporting
confidence: 65%
“…Consequently, it could be suggested that variations in sensory input within each experiment could contribute to differences in the response to CB stimulation. Given that variations in both somatosensory and auditory input appear to primarily modify the later TEP peaks [45, 47], which were intentionally omitted from the analysis of the current study, we believe that the influence of this potential confound is minimal. However, as we cannot completely exclude this possibility, it will be important for future studies deriving EEG measures of CB-C connectivity to also include direct comparisons between sham and real stimulation over CB.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from two separate studies, we show effective and conservative extraction of AEP with younger adult as well as an older population, with variations of sham stimulation protocols, and with different TMS devices and EEG systems. Of note, one of the sham stimulation protocols included electrical stimulation of the skin, as this is increasingly considered an important element of an effective sham design 18 , 77 . We show this method may preserve residual TEP in early, mid and late latency windows.…”
Section: Discussionmentioning
confidence: 99%
“…Movement associated with TMS-evoked scalp muscle contraction can cause additional decay artifacts which persist for longer (>50 ms) and are often hard to distinguish from decay artifacts associated with charges stored within the skin-electrode-amplifier circuit (Rogasch et al, 2014). The often-strong sensations resulting from TMS-evoked muscle activity or from stimulation of other cranial nerves running across the scalp, may also result in somatosensory-evoked potentials (Conde et al, 2019;Gordon et al, 2021). There is some debate as to whether these potentials are directly visible in the scalp EEG (Paus et al, 2001;Rocchi et al, 2021), however other work has shown an increase in potentials around 100-200 ms with increasing electrical stimulation to the scalp (Gordon et al, 2021).…”
Section: Concurrent Tms-eeg: the Challenge Of Artifactsmentioning
confidence: 99%
“…The often-strong sensations resulting from TMS-evoked muscle activity or from stimulation of other cranial nerves running across the scalp, may also result in somatosensory-evoked potentials (Conde et al, 2019;Gordon et al, 2021). There is some debate as to whether these potentials are directly visible in the scalp EEG (Paus et al, 2001;Rocchi et al, 2021), however other work has shown an increase in potentials around 100-200 ms with increasing electrical stimulation to the scalp (Gordon et al, 2021). The discomfort caused by TMS-evoked muscle activity can also result in jaw or facial tension, which causes high levels of ongoing muscle activity in the EEG signal, particularly in lateral electrodes overlying muscles.…”
Section: Concurrent Tms-eeg: the Challenge Of Artifactsmentioning
confidence: 99%